2019
DOI: 10.18415/ijmmu.v6i5.1111
|View full text |Cite
|
Sign up to set email alerts
|

Authority and Position of Notary Deed in the Land Sector

Abstract: The notary public officials are authorized to make an authentic deed, besides other prescribed by statute the authority. At the time of the enactment UUJN No. 30 Tahun 2004, a debate emerged related to the authority notaries in making the deed associated with land. It is in the trigger because of other dignitaries in this PPAT who also has the authority in making the deed associated with land. In the process of land registration as mentioned in PP No. 24 Tahun 1997, that which, aids the head of the land office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This research uses empirical normative juridical research method, a study conducted using secondary data sources that include primary legal materials in the form of norms, basic rules, laws, and regulationsthen coupled with secondary legal materials, namely legal materials used to support primary legal materials 8 . In contrast, empirical approach methods are carried out by conducting interviews in the field.…”
Section: Methodsmentioning
confidence: 99%
“…This research uses empirical normative juridical research method, a study conducted using secondary data sources that include primary legal materials in the form of norms, basic rules, laws, and regulationsthen coupled with secondary legal materials, namely legal materials used to support primary legal materials 8 . In contrast, empirical approach methods are carried out by conducting interviews in the field.…”
Section: Methodsmentioning
confidence: 99%
“…Notaris Publik adalah pejabat berwenang untuk membuat akta otentik selama pembuatan akta otentik tertentu tidak khusus untuk pejabat publik lainnya. Pembuatan akta otentik tidak hanya diwajibkan oleh undang-undang untuk menciptakan kepastian hukum, ketertiban dan perlindungan hukum, tetapi juga karena diinginkan oleh pihak terkait untuk memastikan hak dan kewajiban para pihak demi kepastian hukum dan perlindungan bagi pihak-pihak yang berkepentingan serta bagi masyarakat secara keseluruhan (Pratiwi, Fendri, & Bennie, 2019).…”
Section: Akta Oleh Notarisunclassified
“…Meanwhile, the study conducted by Putri et al (2019) about the authority of a notary public in resolving land disputes with a deed of peace, showed that 1) Notary was authorized to make a peace deed to guarantee legal certainty for the parties to settle land disputes in accordance with article 15 Paragraph (2) letter f of the UUJN and 2) The peace deed drawn up by a Notary Public is an Authentic Deed but not final binding like a van dading deed decided from the results of mediation in court. In addition, another similar study has been conducted by Pratiwi et al (2019) about 'Authority and Position of Notary Deed in the Land Sector'. The result of this study showed that notary as official authorized to make authentic deed has been regulated in the legislation.…”
Section: Introductionmentioning
confidence: 99%